Teachers ' Perceptions of the Integration of Maqasid Sharia in Lesson Planning and Assessment Design - Riska Rahayu; Haryati Haryati; Gina puspita (Islamic Journal of Teaching and Learning, 2025)
The integration of Maqashid Sharia values into the educational process represents a strategic approach to instilling Islamic principles holistically within learning activities. However, many educators still face challenges in understanding and applying Maqashid Sharia principles in lesson planning and assessment design. This study aims to explore teachers’ perceptions of integrating Maqashid Sharia into lesson plans (Rencana Pelaksanaan Pembelajaran or RPP) and student assessment, while also identifying the supporting and inhibiting factors in its implementation. A qualitative case study design was employed, involving Islamic Religious Education (IRE) teachers at selected high schools through purposive sampling. Data were collected via in-depth interviews, RPP and assessment instrument analysis, as well as focused group discussions. Thematic analysis was conducted through coding, categorization, and narrative interpretation. Findings indicate that while most teachers possess a sound conceptual understanding of Maqashid Sharia objectives, they often struggle to operationalize these values systematically within instructional and assessment practices. Supporting factors include value-based training and curriculum integration, whereas inhibiting factors comprise limited pedagogical resources, lack of professional mentoring, and the absence of Maqashid Sharia-aligned indicators in the national assessment system. This study highlights the urgent need to enhance teacher capacity through structured training and the incorporation of contextualized Islamic values into educational policy and practice.